Radiation patterns and gain for a nominal aperture of 105 meters in the Arecibo spherical reflector. - Love, Allan W.
An analysis is presented and the performance of a sub-aperture of the diameter 105 meters in the Arecibo reflector is predicted for a scalar horn feed, the location of the phase center of which is chosen to minimize the effects of spherical aberration. It is shown that a high gain, reasonably good efficiency, and very good pattern performance can be attained over the range of 1 to 1.5 GHz with a single horn. A higher gain with lesser efficiency is achievable up to 3.0 GHz, by changing to a feed optimized for higher frequencies.
Keywords: Antenna radiation patterns; Antenna theory; Antennas; Micorwave antennas; Physical optics; Radio astronomy; Reflector antennas; Spherical antennas